Work motivation and public service motivation: disentangling varieties of motivation and job satisfaction. Issue 10 (3rd October 2018) - Breaugh, Jessica; Ritz, Adrian; Alfes, Kerstin
ABSTRACT: Research on motivation in the public sector has used public service motivation (PSM) and self-determination theory (SDT) interchangeably. This paper compares both theories, develops hypotheses pertaining to their assumptions, and empirically tests them in two public offices in Switzerland. We then explore their relationship with job satisfaction as an indicator of predictive validity. We find that SDT and PSM display conceptual differentiation and SDT has a strongest relationship to job satisfaction. However, moderation analysis suggests that employees with high levels of PSM have more stable job satisfaction compared to their low-PSM counterparts.